Continuous remote ischemic conditioning attenuates cognitive and motor deficits from moderate traumatic brain injury. Issue 1 (July 2018) - Pandit, Viraj; Khan, Muhammad; Zakaria, El Rasheid; Largent-Milnes, Tally M.; Hamidi, Mohammad; O'Keeffe, Terence; Vanderah, Todd W.; Joseph, Bellal
Abstract : BACKGROUND: While studies show that single-dose remote ischemic conditioning (RIC) improves outcomes, the effect of continuous (daily) RIC is unknown. Thus, we aimed to investigate the role of continuous RIC on cognitive and motor function following traumatic brain injury (TBI). METHODS: We subjected 24 male C57BL mice to a cortical-controlled TBI. Two hours after TBI, the animals were randomly allocated to the RIC group (n = 12) or the sham group (n = 12). Remote ischemic conditioning was induced by noninvasive external compression of the hind limb using an occlusive band (six 4-minute cycles/24 hours) for six consecutive days. Before TBI, a baseline rotarod test and novel object recognition were performed. Post-TBI rotarod and novel object recognition tests were performed on Days 1 to 5, 7, 14, and 21. After the animals were sacrificed on Day 21, brain sections were analyzed using hematoxylin and eosin and glial fibrillary acidic protein staining to evaluate the hippocampal CA1 area for neuronal injury. RESULTS: Both the RIC and sham groups had lower latency to fall compared with the baseline post-TBI. The RIC animals had a higher latency to fall compared with the sham animals at all time points, statistically significant after Day 3, until Day 21 post-TBI. Both the RIC and sham groups had lower recognition index compared with the baseline post-TBI. The RIC animals had a significantly higher recognition index than the sham animals after Day 1, until Day 21 post-TBI. Hematoxylin and eosin and glial fibrillary acidic protein staining of the brain samples of the sham group revealed that more neurons in the hippocampal CA1 area appeared shrunken with eosinophilic cytoplasm and pyknotic nuclei compared with the brain samples of the RIC group. CONCLUSION: Postinjury continuous RIC resulted in improved cognitive functions and motor coordination in a mouse model of moderate TBI. Further studies are required to determine optimum dosage and frequency of this novel therapy to maximize its beneficial effects following TBI.